Alzheimer’s disease like neuropathology in Down syndrome cortical organoids - Zhao, Helen H.; Haddad, Gabriel G. (Frontiers in Cellular Neuroscience, 2022)
Down syndrome (DS) is a genetic disorder with an extra copy of chromosome 21 and DS remains one of the most common causes of intellectual disabilities in humans. All DS patients have Alzheimer’s disease (AD)-like neuropathological changes including accumulation of plaques and tangles by their 40’s, much earlier than the onset of such neuropathological changes in AD patients. Due to the lack of human samples and appropriate techniques, our understanding of DS neuropathology during brain development or before clinical onset of the disease remains largely unexplored at the cellular and molecular level. With the advancement of induced pluripotent stem cell (iPSC) technology, iPSC-derived 3D cortical organoids allow us not only to model neurodevelopmental disorders such as in Down syndrome, but also explore the earliest cellular and molecular changes during DS fetal brain development. Here, we report that DS iPSCs have a decreased growth rate than control iPSCs due to a decreased cell proliferation. DS iPSC-derived cortical organoids have a much higher immunoreactivity of amyloid beta (Aß) antibodies and a significantly higher amount of amyloid plaques than control organoids. Although Elisa results did not detect a difference of Aß40 and Aß42 level between the two groups, the ratio of Aß42/Aß40 in the detergent-insoluble fraction of DS organoids was significantly higher than control organoids. Furthermore, an increased Tau phosphorylation (pTau S396) in DS organoids was confirmed by immunostaining and western blot. Elisa data demonstrated that the ratio of insoluble Tau/total Tau in DS organoids was significantly higher than control organoids. In conclusion, a) DS iPSC-derived cortical organoids mimic AD-like pathophysiologyical phenotype in vitro, including abnormal Aß and insoluble Tau accumulation, and b) the molecular neuropathologic signature of AD is present in DS much earlier than predicted, even in early fetal brain development, illustrating the notion that brain organoids maybe a good model to study early neurodegenerative conditions.